Effects of three intramedullary pinning techniques on pin location and articular damage in the canine humerus - Sissener, T. R.; Jones, E.; Langley-Hobbs, S. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The purpose of this study was to compare the pin location and articular damage for intramedullary (IM) pins inserted into the humerus in a directed retrograde, non-directed retrograde, and normograde fashion. Proximal pin positioning in the humerus was significantly more cranial (p<0.05) using both retrograde techniques when compared to the normograde technique, although this did not cause significant interference with anatomical structures. The distance to the biceps tendon, transverse humeral ligament, and the distal pin location was similar with all insertion techniques, however two of ten pins passed in a non-directed retrograde fashion penetrated the shoulder joint. The results of this study suggest that although non-directed retrograde pinning cannot be recommended, either normograde or retrograde pins directed craniolaterally provide acceptable techniques for insertion of IM pins during distal humeral fracture repair.
Keywords: Intramedullary pin; humerus; normograde; retrograde; canine